The Impact of Capital Structure on profitability: Empirical analysis of non-financial companies listed on Bursa Malaysia - Djerfi Abderahmane; Chaalal Cherif Abdelillah (Journal of North African Economies, 2025)
The paper examines the different effects of capital structure on the profitability of the 100 largest non-financial companies listed on Bursa Malaysia for the period 2017-2020. The panel data was used in STATA 15.0 software. Driscoll/Kray and the panel-corrected standard errors (PCSE) were also selected to address econometric problems and to improve the accuracy of the regression coefficients. In this paper, profitability is measured by return on assets and return on equity). The relationship between TL (Total Debt on Total Assets) and ROA and ROE is not significant. CL (Short Term Debt on Total Assets) had a significant positive relationship with return on assets but no significant relationship with ROE. LIQ (liquidity) is also significantly negatively correlated with return on assets and significantly positively with return on equity. This guide provides new insight to corporate managers on how to improve profitability through their capital structure.